Novel Method for Optimal Synthesis of 5G Millimeter Wave Linear Antenna Array - Zarko Rosic; Olivera Mihic; Danijela Aleksic; Dejan Drajic (International Journal of Antennas and Propagation)
We will propose a useful method for 5G mm wave antenna array synthesis, based on Genetic Algorithm for the synthesis of linear array with nonuniform interelement spacing. Our design method was used to obtain the optimal position of the elements in order to get the minimum side lobe level and nulls in desired directions. The simulation results verify that proposed method outperforms the previously published methods in terms of suppression side lobe level while maintaining nulls in specified directions. The flexibility of proposed algorithm shows good potential for the antenna array synthesis.